2019
DOI: 10.1158/2159-8290.cd-18-1175
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the Clinical Development of PI3K Inhibitors: Strategies to Improve Their Impact in Solid Tumors

Abstract: The PI3K pathway is mutated and aberrantly activated in many cancers and plays a central role in tumor cell proliferation and survival, making it a rational therapeutic target. Until recently, however, results from clinical trials with PI3K inhibitors in solid tumors have been largely disappointing. Here, we describe several factors that have limited the success of these agents, including the weak driver oncogenic activity of mutant PI3K, suboptimal patient selection in trials, drug-related toxicities, feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 81 publications
2
112
0
Order By: Relevance
“…In addition to the aforementioned cellular processes in cancer, Akt activation is also associated with resistance to both chemotherapeutic agents and target agents (Clark et al, 2002). Hence, Akt activity may be a potential therapeutic target and biomarker (Navid and Gerber, 2012;Thorpe et al, 2015;Mundi et al, 2016); however, no significant results have been reported from clinical trials with PI3K/Akt inhibitor monotherapy in solid tumors (Hanker et al, 2019). In addition, the use of PI3K/Akt inhibitors in ovarian cancer is scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned cellular processes in cancer, Akt activation is also associated with resistance to both chemotherapeutic agents and target agents (Clark et al, 2002). Hence, Akt activity may be a potential therapeutic target and biomarker (Navid and Gerber, 2012;Thorpe et al, 2015;Mundi et al, 2016); however, no significant results have been reported from clinical trials with PI3K/Akt inhibitor monotherapy in solid tumors (Hanker et al, 2019). In addition, the use of PI3K/Akt inhibitors in ovarian cancer is scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, recent studies demonstrated that the isoform β of PI3K specifically contributes to invasion of breast cancer cells through the regulation of invadopodia maturation (Erami et al, 2019). Since usage of isoform-specific inhibitors can limit the toxicity of panPI3K inhibitors (Hanker et al, 2019) it will be important to test which isoform of PI3K plays a predominant role in AXL-driven invasion. Of note, FDA recently approved Alpelisib (BYL719) as the first PI3K inhibitor, specific for the α isoform, for the treatment of advanced and metastatic breast cancer (FDA, May 24, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Once activated by upstream signals, the PI3K regulatory subunit p85α binds to the phospho-tyrosine residues on receptor protein kinases or adaptor proteins, such as insulin receptor substrate 1 (IRS1), and unleashes the PI3K catalytic subunit p110α (encoded by the PIK3CA gene), which is enabled to phosphorylate phosphatidylinositol 4,5-bisphosphate (PIP2) to phosphatidylinositol 3,4,5-triphosphate (PIP3) ( Fig. 1) [14,15]. On the other hand, mutated (i.e., constitutively active) PI3K subunits catalyze PIP3 biosynthesis independently of upstream signals; in particular, mutations of the PIK3CA gene are found in approximately 40% of HR+ HER2− BCs and cause constitutive PI3K activation [16,17].…”
Section: Main Textmentioning
confidence: 99%
“…Among these alterations, PIK3CA mutations are by far the most common ones [16]. Oncogenic PIK3CA mutations include the following: the kinase domain H1047R mutation (exon 20), which results in higher binding affinity of PI3K to the plasma membrane and to PIP2; the helical domain E542K and E545K mutations (exon 9), which enable the direct interaction of PI3K catalytic subunit with IRS1 independently of p85 and IRS1 phosphorylation; and deletions in the C2 domain, which unleash inhibitory contacts with regulatory subunits [13,14].…”
Section: Main Textmentioning
confidence: 99%